Development of an end-to-end automated production concept for extrusion-based additive manufacturing of personalized medical scaffolds - Janning, Kai; König, Sven; Herbst, Laura; Nießing, Bastian; Schmitt, Robert H. (Frontiers in Manufacturing Technology, 2025)
IndroductionPersonalized medical devices, especially scaffold-based implants, are increasingly important in medical care. One established manufacturing method for these products is extrusion-based 3D printing, also called 3D material extrusion (MEX) or extrusion additive manufacturing (EAM). According to the current state of the art, this technique lacks scalability, as many adjacent processes, such as material handling or quality control, are still carried out manually and no holistically automated solutions have been established.MethodsThis work examines the extrusion-based 3D printing process for manufacturing cell-free porous scaffolds. Based on a literature review, relevant process parameters for MEX and quality attributes of polymer-based scaffolds are analyzed to derive functional requirements for holistically automating the manufacturing process. A concept for an end-to-end automated production infrastructure is developed, to allow efficient and scalable manufacture of scaffolds. All process parameters are analyzed for their influence on the quality attributes, and requirements are specified. Based on this, the development of the production concept is systematically carried out.ResultsThe resulting technical system consists of a magnetic planar drive, which is used as an intralogistic transport system, but also forms the horizontal axis plane of the 3D printer. The resulting frictionless levitating print bed increases cleanroom suitability and enables the parallelization of print jobs and quality control steps for improved production flexibility and scalability. The central approaches of the concept are presented in a physical demonstrator.DiscussionAn initial proof of concept for planar drive-based MEX is provided and lays the foundation for further development and validation of the conceptualized production infrastructure.